Current and Historical Trends in Diversity by Race, Ethnicity, and Sex Within the US Pathology Physician Workforce. Issue 4 (12th August 2020) - White, Marissa J; Wyse, Rhea J; Ware, Alisha D; Deville, Curtiland
Abstract: Objectives: This study assessed historical and current gender, racial, and ethnic diversity trends within US pathology graduate medical education (GME) and the pathologist workforce. Methods: Data from online, publicly available sources were assessed for significant differences in racial, ethnic, and sex distribution in pathology trainees, as well as pathologists in practice or on faculty, separately compared with the US population and then each other using binomial tests. Results: Since 1995, female pathology resident representation has been increasing at a rate of 0.45% per year (95% confidence interval [CI], 0.29-0.61; P < .01), with pathology now having significantly more females (49.8%) compared to the total GME pool (45.4%; P < .0001). In contrast, there was no significant trend in the rate of change per year in black or American Indian, Alaskan Native, Native Hawaiian, and Pacific Islander (AI/AN/NH/PI) resident representation ( P = .04 and .02). Since 1995, underrepresented minority (URM) faculty representation has increased by 0.03% per year (95% CI, 0.024-0.036; P < .01), with 7.6% URM faculty in 2018 (5.2% Hispanic, 2.2% black, 0.2% AI/AN/NH/PI). Conclusions: This assessment of pathology trainee and physician workforce diversity highlights significant improvements in achieving trainee gender parity. However, there are persistent disparities in URM representation, with significant underrepresentation of URM pathologists compared with residents.